Detention and arrest - Coughlan, Stephen Gerard (Irwin Law, 2024)
"The criminal justice system aims to maintain a balance between the individual interest of private citizens to carry on their lives free from state interference, and the communal interest in maintaining a safe society. These two goals come into conflict with each other most visibly when agents of the state take control of private citizens–that is, when they exercise their powers to detain or to arrest. The book focuses on “street-level” encounters: detentions and arrests that occur in the course of investigating crime and laying charges. The authors explore the initial interaction between agents of the state or others authorized to detain and arrest, and the private citizens whose liberty is interfered with. It is at that point that the balance between societal safety and individual liberty is most keenly in play. This third edition has been updated to incorporate significant statutory changes to Part XVI of the Criminal Code (Compelling Appearance of Accused Before a Justice and Interim Release), to common law powers (powers of detention, safety searches, search incident to arrest, etc.), to developments in the law in deaing with racial profiling, and to Charter rights (freedom from arbitrary detention, right to counsel, and so on)."– Provided by publisher.